Revealing the diversity of Cloeodes Traver, 1938 (Ephemeroptera: Baetidae) in the Neotropics: description of eleven new species from Brazilian mountain ranges - Salles, F.f.; Massariol, F.c.; Angeli, K.b.; Lima, M.m.; Gattolliat, J-L.; Sartori, M. (Zootaxa, 2015)
In the present work, based on material from distinct mountain ranges in Brazil, 11 new species of Cloeodes with hind wings or hind wing pads are described, illustrated and discussed. Among the new species, in C. aiuruoca, C. amantykyra, C. atlanticus, C. boldrinii and C. ioachimi, the apex of the fore femora in the nymphs is extremely projected (a characteristic previously found only in two species of the genus). Cloeodes guara and C. tracheatus share the presence of unusual large and dark gills. Cloeodes melanotarsus is readily distinguished by conspicuous blackish tarsi, C. lucifer by the bright yellow coloration of tergum I, and C. xyrognathos by blade-like incisors. Cloeodes magnus, besides being the largest species of the genus, with a body size reaching 12 mm, possess short maxillary palp. Comments on the presence of C. irvingi and C. opacus in Brazil are also provided. An interactive online key is provided for the nymphs of all the species of Cloeodes in which hind wing pads are present.